Literature Review: The Effectiveness of Electronic Medical Records (RME) On Hospital Service Quality - Indira, Zahrasita Nur; Widodo, Aris Puji; Agushybana, Farid (Universitas Teuku Umar, 2023)
Health Information System is a systematic way of managing information at all levels of government to provide healthcare services to the community. In providing services to the community, the health information system is a systemic management of information at all levels of government. Every healthcare facility in Indonesia must maintain electronic medical records based on Permenkes No. 24/2022. This shows that the role of Health Information Systems is needed in a health system. However, using electronic medical records (EMR) in Indonesian healthcare facilities must be uniformly and sufficiently implemented, so it cannot provide accurate and timely data. This study aims to assess the implementation of EMR in Indonesian hospitals. This study used the literature review method by reviewing 15 journal articles published between 2016 and 2022, retrieved through Google Scholar. The results showed that several hospitals in Indonesia had implemented EMR; some hospitals have effectively implemented it and benefit from the implementation of EMR, such as improving the efficiency of time and effort in providing health services to patients. Patients also receive better medical care. The study findings aim to encourage all healthcare facilities to optimize the use of EMR to enhance healthcare services.